Artificial Intelligence Technology in Basketball Training Action Recognition - Cheng, Yao; Liang, Xiaojun; Xu, Yi; Kuang, Xin (Frontiers in Neurorobotics, 2022)
the primary research purpose lies in studying the intelligent detection of movements in basketball training through Artificial Intelligence (AI) technology. Primarily, the theory of somatosensory gesture recognition is analyzed, which lays a theoretical foundation for research. Then, the collected signal is denoised and normalized to ensure that the obtained signal data will not be distorted. Finally, four algorithms, Decision Tree (DT), Naive Bayes (NB), Support Vector Machine (SVM), and Artificial Neural Network (ANN), are used to detect the data of athletes’ different limbs movements and recall. The accuracy of the data is compared and analyzed. Experiments show that the Back Propagation (BP) ANN algorithm has the best action recognition effect among the four algorithms. In basketball training athletes' upper limbs movement detection, the average accuracy rate is close to 93.3%, and the average recall is also immediate to 93.3%. In basketball training athletes' lower limbs movement detection, the average accuracy rate is close to 99.4%, and the average recall is immediate to 99.4%. In the detection of upper limbs and lower limbs movements: the recognition method can efficiently recognize the basketball actions of catching, passing, dribbling, and shooting, the recognition rate is over 95%, and the average accuracy of the four training actions of catching, passing, dribbling and shooting is close to 98.95%. The intelligent basketball training system studied will help basketball coaches grasp the skilled movements of athletes better to make more efficient training programs and help athletes improve their skill level.